Aging study of a lead-acid storage bank in a multi-source hybrid system - El Mehdi Laadissi; Jaouad Khalfi; Fouad Belhora; Chouaib Ennawaoui; Abdessamad El Ballouti (Institute of Advanced Engineering and Science, 2020)
Autonomous and grid-connected systems play an important role in the massive integration of renewable energy sources necessary for the global development of a sustainable society. In this regard, the analysis of the behavior of electrochemical storage devices such as lead-acid batteries installed on hybrid energy systems and microgrids in terms of lifespan and economic profitability is an important research subject. The purpose of this article is to present a methodology for calculating the aging rate of a storage battery inserted in a hybrid multisource system. The approach consists in first knowing the solicitations of the battery during a year knowing at every moment its state of charge. This curve is obtained from a dynamic simulator taking into account the intermittences of the sources and the load. The second step is to determine the number of cycles and the depth of discharge of each from the stat of charge. Finally, based on the battery life characteristic given by the manufacturer (cycle number vs. discharge depth), the aging rate of the battery for one year of operation is determined.